2016
DOI: 10.1038/srep39207
|View full text |Cite
|
Sign up to set email alerts
|

An Exceptionally Facile Two-Step Structural Isomerization and Detoxication via a Water-Assisted Double Lossen Rearrangement

Abstract: N-hydroxyphthalimide (NHPI), which is best known as an organocatalyst for efficient C-H activation, has been found to be oxidized by quinoid compounds to its corresponding catalytically active nitroxide-radical. Here, we found that NHPI can be isomerized into isatoic anhydride by an unusually facile two-step method using tetrachloro-1,4-benzoquinone (TCBQ, p-chloranil), accompanied by a two-step hydrolytic dechlorination of highly toxic TCBQ into the much less toxic dihydroxylation product, 2,5-dichloro-3,6-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 53 publications
(82 reference statements)
0
6
0
1
Order By: Relevance
“…In our present work, these findings demonstrate that dG can be effectively oxidized to mutagenic products dIz, dZ, and 8-oxodG by XBQs together with organic hydroperoxides independent of redox-active transition-metal ions. Since halogenated quinones are observed as reactive oxidation intermediates or products in processes used to oxidize or destroy polychlorinated POPs in various chemical and enzymatic systems, the above results may partly explain the potential carcinogenicity of not only PCP but also other widely used polyhalogenated aromatic compounds. , Recently, 12 polyhalogenated quinones including TCBQ, which contribute to an increased risk of developing bladder cancer, were identified as new chlorination disinfection byproducts in drinking water and swimming pool water. , Since organic hydroperoxides such as 13-HPODE can be formed through both the nonenzymatical reaction of polyunsaturated fatty acids and enzymatical oxidation of linoleic acid and arachidonic acid, it is possible that halogenated quinones and organic hydroperoxides could make an essential contribution to the genotoxicity of halogenated quinones. Therefore, our new findings may have interesting and potential implications in the fields of biology and environment.…”
Section: Resultsmentioning
confidence: 99%
“…In our present work, these findings demonstrate that dG can be effectively oxidized to mutagenic products dIz, dZ, and 8-oxodG by XBQs together with organic hydroperoxides independent of redox-active transition-metal ions. Since halogenated quinones are observed as reactive oxidation intermediates or products in processes used to oxidize or destroy polychlorinated POPs in various chemical and enzymatic systems, the above results may partly explain the potential carcinogenicity of not only PCP but also other widely used polyhalogenated aromatic compounds. , Recently, 12 polyhalogenated quinones including TCBQ, which contribute to an increased risk of developing bladder cancer, were identified as new chlorination disinfection byproducts in drinking water and swimming pool water. , Since organic hydroperoxides such as 13-HPODE can be formed through both the nonenzymatical reaction of polyunsaturated fatty acids and enzymatical oxidation of linoleic acid and arachidonic acid, it is possible that halogenated quinones and organic hydroperoxides could make an essential contribution to the genotoxicity of halogenated quinones. Therefore, our new findings may have interesting and potential implications in the fields of biology and environment.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to gcd , the phosphate-specific transport ( pst ) system is used for free inorganic phosphate transport in Bacillus subtilis and Escherichia coli . The pst operon of E. coli and B. subtilis is composed of pstS, pstC, pstA , and pstB as well as a two-component signal transduction system consisting of phoP / phoR for phosphate uptake (Xie et al 2016 ). In the present study, genomic analyses of LK11 revealed that it also carries the pst operon ( pstA, pstB, pstC , and pstS genes; locus AV944_10605, locus AV944_10610, locus AV944_10600, and locus AV944_10615, respectively), as well as phoB (locus AV944_10590), phoP (locus AV944_05370), and phoR (locus AV944_10620) genes for phosphate transport.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we found that the rate of the first step reaction in eq was faster with the increasing numbers of chlorines on the quinones ring. , Therefore, the rate of this step might depend on the redox potential of C n BQs, the rate of nucleophilic substitution increased with the increasing one-electron reduction potentials. More specifically, during our recent study on the reaction mechanism of C n BQ/hydroxamic acids, we found that the rate of Lossen rearrangement reaction of C n BQ/benzohydroxamic acid (BHA) is directly proportional to the acidity of the leaving group ( C n –1 BQ–OHs) (eq ). …”
Section: Resultsmentioning
confidence: 99%